Assessment of Basalt Soil Quality under Different Land Use Types in Bao Loc - Di Linh Area, Lam Dong Province - Thuy, Nguyen Thi; Anh, Luu The (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 3DO - 10.25073/2588-1094/vnuees.4117, 2017)
Basaltic soil is considered as the most advantageous soil unit in comparison with other units of the Central Highlands, that distributed mainly in the plateaus of Kon Plong, Kon Ha Nung, Pleiku, Buon Ma Thuot, M'Drak, Dak Nong and Di Linh - Bao Loc. Much of the basaltic soil in the Central Highlands has been used for cultivation of long-term industrial crops. Currently, due to massive forest destruction for developing long-term industrial trees in the basaltic soil in Bao Loc - Di Linh, the natural fertility of the basaltic soil has been remarkably reduced. The physical and chemical properties of the basaltic soil under different land use types have decreased sharply compared to basaltic soil under the natural forest. The average rate of decline of total organic matter content of plantation forest land is 16%, overused forest land is 44%, tea land is 46%, coffee land is 60% compared to the same soil unit under the natural forest. The cation exchange capacity (CEC), content of total nutrients and plant available nutrients under the land use types were also decreased significantly compared to the soil unit under the natural forest. The changes of physical and chemical properties of the basaltic soil with coffee cultivation was highest in comparison with other land use types. The organic matter and potassium are two limiting factors of the nutrients in the basaltic soil of the study area, especially for tea cultivation. Keywords Basaltic soil, soil properties, CEC, Bao Loc - Di Dinh References [1] Lưu Thế Anh và nnk, 2015. Nghiên cứu tổng hợp thoái hóa đất, hoang mạc hóa ở Tây Nguyên và đề xuất các giải pháp sử dụng đất bền vững. Báo cáo tổng kết đề tài cấp Nhà nước thuộc Chương trình Tây Nguyên 3, mã số TN3/T01. [2] Nguyễn Đình Kỳ, Lưu Thế Anh, 2006. Thực trạng thoái hóa đất basalt Tây Nguyên và các giải pháp sử dụng hợp lý bảo vệ tài nguyên - môi trường đất. Kỷ yếu Hội nghị khoa học Địa lý toàn quốc lần thứ II, tr.468-482. [3] Viện Quy hoạch và Thiết kế Nông Nghiệp, 2005. Báo cáo thuyết minh bản đồ đất tỉnh Lâm Đồng. [4] Sở Tài nguyên và Môi trường tỉnh Lâm Đồng, 2013. Kết quả kiểm kê đất đai tỉnh Lâm Đồng năm 2012. [5] Bộ Nông nghiệp và Phát triển nông thôn, 2009. Cẩm nang sử dụng đất. Nhà xuất bản Khoa học và Kỹ thuật, Hà Nội. [6] Đỗ Đình Sâm và Nguyễn Ngọc Bình, 2000. Đánh giá tiềm năng sản xuất đất lâm nghiệp Việt Nam. Nhà xuất bản Nông nghiệp, Hà Nội. [7] Hội Khoa học Đất Việt Nam, 2000. Đất Việt Nam. Nhà xuất bản Nông nghiệp, Hà Nội. [8] Trần Kông Tấu, 2006. Tài nguyên đất. Nhà xuất bản Đại học Quốc gia Hà Nội, Hà Nội.